Pharmaceutical Prices: The Impact of the Launch Strategy - An Analysis of German Data - Yvonne-Beatrice Böhler; Christian Lamping; Philipp C. Wichardt (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper reports the results from a statistical analysis of pharmaceutical price negotiations in Germany, where the pricing system was changed in 2011 in order to tie prices more to the benefits of the pharmaceuticals. A multiple linear regression of 187 pharmaceuticals which were assessed from 2011 to 2017 suggests that, despite the change, the manufacturers' launch strategy (freely chosen first year price) still has a major impact on pricing while the impact of the additional benefit remains comparably small. Moreover, the data suggest that the assessment of the Federal Joint Committee - while not yet existing at the point - best explains the manufacturer's launch strategy, indicating that manufacturers know more than they reveal.
Keywords: I10; 330; AMNOG; early benefit; assessment; pharmaceuticals